The merchant prince of Black Chicago : Anthony Overton and the building of a financial empire - Weems, Robert E., 1951- (University of Illinois Press, 2020)
"Born to enslaved parents, Anthony Overton became one of the leading African American entrepreneurs of the twentieth century. Overton's Chicago-based empire ranged from personal care products and media properties to insurance and finance. Yet, despite success and acclaim as the first business figure to win the NAACP's Spingarn Medal, Overton remains an enigma. Robert E. Weems Jr. restores Overton to his rightful place in American business history. Dispelling stubborn myths, he traces Overton's rise from mentorship by Booker T. Washington, through early failures, to a fateful move to Chicago in 1911. There, Overton started a popular magazine aimed at African American women that helped him dramatically grow his cosmetics firm. Overton went on to become the first African American to head a major business conglomerate, only to lose significant parts of his businesses-and his public persona as "the merchant prince of his race"-in the Depression, before rebounding once again in the early 1940s. Revealing and panoramic, The Merchant Prince of Black Chicago weaves the fascinating life story of an African American trailblazer through the eventful history of his times"--